EFEKTIVITAS SENAM AEROBIKLOW IMPACT TERHADAP KUALITAS TIDUR PADA MAHASISWA - Rosembrina, Rosembrina; Deli, Hellena; Woferst, Rismadefi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2021)
Students are individuals who tend to have poor sleep quality, so that it needs immediate treatment. Among the nonpharmacological treatments is low-impact aerobic exercise. The purpose of this research is to know the effectiveness of low-impact aerobic exercise on improving student sleep quality. Quasi-experimental were used in this study using a non-equivalent control group approach. Samples were 34 respondents (divided equally into2 groups) recruited using a purposive sampling technique.The experimental group was given intervention for 60 minutes per day, while the control group was not given any treatment. The data analysis used was univariate analysis to see frequency and bivariate analysis with dependent t test and the wilcoxon alternative test.The result of statistical tests show that there is a significant difference of sleep quality before and after the intervention with p value 0,000 (<0,05). The result showed that the low-impact aerobic exercise can improve sleep quality in students. The results of this study can be used as a reference for using low impact aerobic exercise as an alternative in resolving sleep quality disturbances in students. Keywords: Students, low-impact aerobic exercise, sleep quality